2022
DOI: 10.3389/fgene.2022.845474
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Constellation of Killer Cell Immunoglobulin-Like Receptors and Cognate HLA Class I Ligands that Controls Natural Killer Cell Antiviral Immunity Predisposes COVID-19

Abstract: Background: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection causes coronavirus disease-2019 (COVID-19) in some individuals, while the majority remain asymptomatic. Natural killer (NK) cells play an essential role in antiviral defense. NK cell maturation and function are regulated mainly by highly polymorphic killer cell immunoglobulin-like receptors (KIR) and cognate HLA class I ligands. Herein, we tested our hypothesis that the individualized KIR and HLA class I ligand combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…found an association between two NK cell immunoglobulin-like receptors (KIR), named KIR2DS4 and KIR3DL1, with an inhibitory and activating function, respectively, and an increased risk of severe disease ( 88 ). Another study reported a significant decrease in the inhibitory KIR receptors in COVID-19 patients compared to healthy controls and a considerable increase in activating KIR receptors in patients with a severe disease ( 89 ) ( Figure 1 ).…”
Section: The Relationship Between the Innate Immune System And The Pr...mentioning
confidence: 96%
See 1 more Smart Citation
“…found an association between two NK cell immunoglobulin-like receptors (KIR), named KIR2DS4 and KIR3DL1, with an inhibitory and activating function, respectively, and an increased risk of severe disease ( 88 ). Another study reported a significant decrease in the inhibitory KIR receptors in COVID-19 patients compared to healthy controls and a considerable increase in activating KIR receptors in patients with a severe disease ( 89 ) ( Figure 1 ).…”
Section: The Relationship Between the Innate Immune System And The Pr...mentioning
confidence: 96%
“…In recent studies, a significant decrease has been observed in the frequency and the absolute numbers of basophils in patients with severe COVID-19 ( 82 , 92 , 93 ). Moreover, a stronger expression of programmed cell death ligand 1 (PD-L1), an inhibitor of T cell activation, has been found on basophils in severe vs. mild COVID-19, correlating with poor disease outcomes ( 89 ).…”
Section: The Relationship Between the Innate Immune System And The Pr...mentioning
confidence: 99%
“…Further protection could derive from interactions between killer-cell immunoglobulin-like receptors (KIRs), expressed on the surface of natural killer (NK) cells and their cognate human leukocyte antigen (HLA) Class I ligands ( 20 , 21 ). A recent study performed on the population of central southern Sardinia showed that KIR2DS2 in combination with HLA-C alleles of the C1 group exerts a potent protective effect against the adverse outcomes of COVID-19 ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Killer cell immunoglobulin–like receptors (KIR) and associated HLA class I ligands are critical regulators of NK cell development and function. Inadequate NK cell maturation and reduced anti-SARS-CoV-2 defense are likely because of a lack of KIR3DL1 + HLA-Bw4 + and KIR3DL2 + HLA-A3 /11 + combinations, which cause COVID-19 (Maruthamuthu et al 2022 ). The KLRC2 gene encodes NKG2C, an activating NK cell receptor that interacts to HLA-E on infected cells to activate NK cells.…”
Section: Hla Associations In Sars-cov-2 Infection and Covid-19 Diseas...mentioning
confidence: 99%